1998
DOI: 10.1074/jbc.273.11.6242
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Functional Analysis of the Substrate Specificity/Catalytic Domains of Human M-form and P-form Phenol Sulfotransferases

Abstract: Human monoamine (M)-form and simple phenol (P)-form phenol sulfotransferases (PSTs), which are greater than 93% identical in their primary sequences, were used as models for investigating the structural determinants responsible for their distinct substrate specificity and other enzymatic properties. A series of chimeric PSTs were constructed by reciprocal exchanges of DNA segments between cDNAs encoding M-form and P-form PSTs. Functional characterization of the recombinant wild-type M-form, P-form, and chimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 32 publications
4
63
0
1
Order By: Relevance
“…In comparison with human SULTs, the K m and k cat values of dmSTs are relatively high. 18) The k cat values of the dmSTs are also significantly higher than that of ceST1. 8) These data suggest that the dmSTs effectively metabolize high concentration phenolic xenobiotics and act as a powerful defense system.…”
Section: Discussionmentioning
confidence: 84%
“…In comparison with human SULTs, the K m and k cat values of dmSTs are relatively high. 18) The k cat values of the dmSTs are also significantly higher than that of ceST1. 8) These data suggest that the dmSTs effectively metabolize high concentration phenolic xenobiotics and act as a powerful defense system.…”
Section: Discussionmentioning
confidence: 84%
“…Preparation of Purified Wild-type and Chimeric SULT1A3/SULT1A1 and Point-mutated SULT1A3s-Wild-type and chimeric SULT1A3 and SULT1A1, cloned/generated and expressed using the pGEX-2TK glutathione S-transferase gene fusion system, were purified using glutathione-Sepharose in conjunction with thrombin cleavage to separate the fusion protein, based on the procedure established previously (7). Pointmutated SULT1A3s were prepared using the QuikChange site-directed mutagenesis kit, expressed using the pGEX-2TK glutathione S-transferase gene fusion system and purified with glutathione-Sepharose followed by thrombin cleavage to separate the fusion protein, as described previously (8).…”
Section: Materials-l-tyrosinementioning
confidence: 99%
“…1B). Characterization of these chimeras indicated that both Regions I and II were indeed critical for the specificity of SULT1A3 for dopamine and of SULT1A1 for p-nitrophenol (7). To extend the study further, we and others (8,10,11) had, by site-directed mutagenesis, exchanged amino acid residues in these two regions between SULT1A3 and SULT1A1.…”
mentioning
confidence: 99%
See 2 more Smart Citations